Analisis Sistem Pengendalian Intern Pendapatan LPP RRI Medan - Parlindungan Parlindungan; Edisah Putra Nainggolan; Lizza Meidina (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to determine the Internal Control System of LPP RRI Medan, and the Income of LPP RRI Medan. This research was conducted at LPP RRI Medan. The approach used is descriptive. The data analysis technique used in this research is the descriptive analysis technique, namely collecting data, clarifying data, explaining data, and analyzing data. The data used in the financial statements of LPP RRI Medan's income for the 2016-2019 period. The data collection technique is done using documentation studies, interviews, and observations, namely studying documents related to the problem of a research data such as company financial data reports obtained directly from the company, interviewing related functions, and also direct observations in the field. The results of this study conclude that the internal control system in increasing the income of LPP RRI Medan has not been fully effective